Electronic navigation systems - Tetley, L. (Laurence) 1941-; Calcutt, D. M. 1935 (Butterworth-Heinemann, 2001)
Maritime navigation has rapidly developed since the publication of the last edition of the title with methods of global position fixing for shipping becoming standardized. As in the previous two editions, this edition will provide a sound basis for the understanding of modern navigation systems and brings the student or professional up-to-date with the latest developments in technology and the growing standardization of maritime navigation techniques